Application of COCA in EFL Writing Instruction at the Tertiary Level in China - Xiao, Gengsheng; Chen, Xin (International Journal of Emerging Technologies in Learning (iJET), 2018)
English writing plays an increasingly important role in the context of globalization. However, Chinese college students’ writing skills of English as a Foreign Language (EFL) are quite deficient and EFL writing instruction at the tertiary level in China is confronted with enormous difficulties. To handle this situation, we suggest the application of Corpus of Contemporary American English (COCA) in college English writing instruction to resolve current problems such as learners’ insufficient exposure to authentic linguistic materials, inactive thinking, lack of motivation to write, and teachers’ heavy workload of making assessment. The application of COCA runs through the whole process of writing. At pre-writing stage, COCA is applied for idea inspiration and vocabulary preparation; at while-writing stage, COCA is used for eliminating erroneous usages and improving language quality, especially lexical accuracy and complexity; at post-writing stage, the application of COCA aims at giving effective feedback by improving the quality of different forms of assessment, i.e. teacher, self- and peer assessment.